2022
DOI: 10.3389/fsurg.2022.966197
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hidden blood loss in unilateral biportal endoscopic lumbar spine surgery

Abstract: BackgroundUnilateral biportal endoscopic (UBE) spine surgery is a minimally invasive procedure for treating lumbar disorders. Hidden blood loss (HBL) is easily ignored by surgeons because blood loss is less visible. However, there are limited studies on HBL in UBE spine surgery. This study aimed to evaluate HBL and its possible risk factors in patients undergoing UBE spine surgery.MethodsPatients with lumbar disc herniation or lumbar spinal stenosis who underwent unilateral biportal endoscopic surgery between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Pearson or Spearman correlation analysis showed that sex may be associated with HBL in the PETD group, with female patients having less HBL than male patients, which may be related to the relatively small amount of bone resection and smaller back muscles in women than in men. Guo et al 18 found that the HBL increases with the thickness of the paraspinal muscles at target levels in the UBE. From this, it could be seen that women have relatively weak back muscles and therefore have less HBL than men.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pearson or Spearman correlation analysis showed that sex may be associated with HBL in the PETD group, with female patients having less HBL than male patients, which may be related to the relatively small amount of bone resection and smaller back muscles in women than in men. Guo et al 18 found that the HBL increases with the thickness of the paraspinal muscles at target levels in the UBE. From this, it could be seen that women have relatively weak back muscles and therefore have less HBL than men.…”
Section: Discussionmentioning
confidence: 98%
“…Wang et al 17 reported that the mean HBL during UBE spine surgery was 469.5±195.3 ml, accounting for 57.6% of TBL. Guo et al 18 reported a mean HBL volume of 361.4±216.8 ml in patients treated with UBE lumbar spine surgery. Hu et al 19 retrospectively analyzed 74 patients diagnosed with LDH and treated with PETD, with an HBL of 341.04±191.15 ml.…”
Section: Discussionmentioning
confidence: 99%
“…The overall complication rate of UBE surgery for lumbar spinal stenosis was 8.1% [29][30] . Among them, dural tear is the most common complication with an incidence of about 1.5-9.7% [31][32][33][34] . While most dural tears are small and can be managed conservatively, dural tears larger than 10mm require repair to prevent cerebrospinal uid leakage and other sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Although UBE may inferior to other spinal endoscopic techniques, it has its own merits which can make it stand out in comparison to the conventional surgeries, for example, the smaller surgical incision, the less pain of patients early after operation, the flexible operation, its wide vision and short learning curve which are worth promoting in primary hospitals. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%